Pengaruh Perbandingan Ubi Jalar Ungu (Ipomoea batatas var ayamurasaki) dan Terigu terhadap Karakteristik Kue Pia - Duniaji A.S Duniaji A.S; Maya Anita Putri; N.L. Ari Yusasrini (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2016)
This study was aimed to determine the effect of purple-fleshed sweet potato and wheat flour ratioon characteristics of Pia cake and to determine the best ratio of purple sweet potato and wheatflour to produce Pia cake with the best characteristics. The experimental design used wascompletely randomized design (CRD) by treatment with purple sweet potato in a row as follows:15%, 20%, 25%, 30%. Each treatment was repeated four times to obtain 16 experimental units.The results showed that the treatment comparison purple-fleshed sweet potato and wheat floureffect on water content, protein content, fat content, and carbohydrate content and the sensoryproperties of Pia cake (color, flavor, texture, and overall acceptance). However, there is nosignificant effect found on ash content, aroma and flavor. The best characteristic of pia cake wasobtained on treatment with purple-fleshed sweet potato ratio of 25% and wheat 75% with 23.12%moisture content, ash content of 0.77%, 8.09% protein content, fat content 8.78%, 58.80%carbohydrate levels and levels of 0.51% anthocyanins. On sensory properties are found that color5.8 (like), the aroma of 5.2 (rather like), flavor 5.6 (like), the texture of 6.05 (like) and the overallacceptance of 6.55 (really like).